Government Spending, Domestic Investment, Human Development Index and Indonesian Gross Domestic Product - Sumarsono, Hadi; Qodri, Lutfi Asnan; Prayitno, Putra Hilmi (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
This research investigates the linkage between government expenditure, domestic investment, national income, human development index, and economic growth in Indonesia during the period 2015-2020. This study applied the quantitative method with Common Effect Model, Fixed Effect Model, and Random effect Model to estimate the empirical model. The data in this research were gathered from these main sources, including Statistics Indonesia and the Indonesian Investment Coordinating Board. The classical assumption is also provided to meet the analysis criteria. The findings of the study indicate that government spending positively impacts Indonesian economic growth. Indeed, national income has a robust effect on economic growth. This study also confirms the crucial role in determining economic growth in Indonesia. Surprisingly, the human development index failed to support a robust spur to economic growth in Indonesia. These results contribute to the literature on economic growth and have tremendous implications for Indonesian policymakers to consider these findings.